Low-ability Students’ learning experiences with technology integration in post- pandemic mathematics classroom - Dahal, Prem Prasad; Ghimire, Nawaraj (Innovative Research Journal, 2025)
The rapid growth in the use of technology enhanced learning during and following the COVID-19 pandemic has had a major impact on the way mathematics education is delivered, especially for students who have low ability. In the context of Nepal and post-pandemic, in order to integrate digital tools, opportunities and challenges were presented to learners who are struggling with mathematical concepts, digital literacy, and academic confidence. This research thus intended to discuss the lived learning experiences of low-ability B.Ed. level students when they encountered technology-integrated post-pandemic mathematics classrooms. Through the descriptive phenomenological design, data were obtained from three B.Ed. level students in the form of structured open-ended questionnaire consisting of 38 reflective questions. Their answers were analyzed by Moustakas' phenomenological procedures that include horizontalization, meaning-unit extraction, thematic clustering, and synthesis of composite essence. The results showed that the learners had the enabling and constraining effects of technology. They reported better visualization, more explanatory and practice opportunities, but also reported challenges with poor internet connectivity and device limitations, low technological confidence, and emotional tension. Four central themes emerged: reconstruction of mathematical identity through technology continued digital barriers, greater engagement through interactive tools, and emotional negotiation in adapting to technological learning.